Graphene film achieves electrostatic protection of ultra-high voltage solar array - Zhang Qi; Lan Zhicheng; Cui Xinyu; Zhang Wei (Dianzi Jishu Yingyong)
Aiming at the problem that the solar array of space power station is prone to electrostatic damage under ultra-high voltage, a graphene transparent conductive film with high transmittance and conductivity is developed to realize zero potential on the packaging surface of the fully flexible solar cell module, and achieve the purpose of charge release. Under the experimental conditions of 750 V ultra-high voltage, the fully flexible solar cell modules encapsulated by graphene film did not show electrostatic discharge and the electrical properties of the solar cell modules did not change, which proved the ability of graphene film in electrostatic protection under ultra-high voltage condition.